Climate change adaptation, gender, and mainstreaming: The role of gender in Fiji's relocation initiative - Bertana, Amanda; Blanton, Natalie (Climate and Development, 2022)
Climate change has elucidated already existing gender inequalities associated with unequal access to resources, decision-making processes, and higher exposure to environmental shocks and stressors. Growing acknowledgment of the gender-differentiated implications of climate change in recent years has placed gender equality as a focal point in international discourses on climate change adaptation. The policy perspective of gender equality is universalized, but how it transcribes in local climate change adaptation projects remains elusive. Using the relocation of Vunidogoloa, Fiji, this article explores the tension and compatibility between the way gender equality is discussed and how it is implemented in climate change adaptation projects. © 2022 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; changements climatiques; discipline; environnement; ethnographie; fidji; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; sécurité alimentaire; thématiques

Coronavirus, domestic labour and care: Gendered roles locked down - Craig, Lyn (Journal of Sociology, 2020)
The Covid-19 pandemic turned daily lives upside down. Lockdowns and physical distancing meant hundreds of thousands of people switched to working from home, significantly blurring the temporal and spatial boundaries between paid work, domestic labour and caring for others. This article explores gender relations, and the division of employment, domestic labour and care, drawing on early results from an online survey, Work and Care in the Time of Covid-19, carried out between 7 May and 4 June 2020.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; australie; care; covid-19; discipline; division sexuelle du travail; océanie; pandémie; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail de reproduction; travail invisible

"I’m strong within myself": Gender, class and emotional capital in childcare - Andrew, Yarrow (British Journal of Sociology of Education, 2015)
Emotions have received increasing attention in educational circles in the last decade. Drawing on Bourdieu, feminist scholars use emotional capital to illustrate the ways gendered inequalities can compound the disadvantages of social class. This paper examines relationships within childcare services in Australia, showing how emotional capital functions as a resource for staff. Data from interviews with childcare staff illustrate key aspects of emotional capital, such as reflexivity, resilience and embodiment. Findings show that investing in emotional capital is the key to a long-lasting commitment to childcare work, and should be valued accordingly. © 2013 Taylor & Francis.
Keywords: 2000 à aujourd'hui; 2010-2019; australie; capital émotionnel; care; discipline; maternité; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; service de garde; sociologie; thématiques; travail; travail du care

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

Feeling beyond rules: Politicising the sociology of emotion and anger in feminist politics - Holmes, Mary (European Journal of Social Theory, 2004)
The part anger plays in motivating political action is frequently noted, but less is said about ways in which anger continues to be a part of how people do politics. This article critically assesses approaches to emotions that emphasize managing anger in accordance with ‘feeling rules’. It reflects on the utility of Marxist notions of conflict as the engine of change for the understanding of how anger operates in political life. This involves understanding the ambivalence of anger and its operation within particular power relations. Shifting sets of conventions have had some continuity in discouraging women in Western nations (particularly white and middle-class women) from showing anger. But clearly, women do get angry and feminists have drawn on anger in acting politically. New Zealand feminist writings from the ‘second wave’ are taken as illustrative of the common difficulties Western feminists faced in dealing with anger. These difficulties were due to trying to juggle social conventions about femininity, the political ideal of sisterhood, and the realities of dealing with other women in often new and experimental political processes. Anger could be personalized and hurtful, but in certain cases its expression was constructive in producing more respectful relations. Exploring these cases makes it clear how anger produces, and is produced by, relations with others.
Keywords: 1900-1999; 1970-1979; 1980-1989; colère; discipline; débat; militance; mouvements féministes; nouvelle-zélande; océanie; périodes historiques; rapports de pouvoir; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Identity, emotion, and feminist collective action - Hercus, Cheryl (Gender and Society, 1999)
This article explores the relationship between identity, emotion, and feminist collective action. Based on interview research, the analysis confirms the central importance of anger in collective action and its particular significance for feminist identity and activism. As an emotion thought deviant for women, the anger inherent in feminist collective action frames created problems for participants in terms of relationships with partners, friends, and work colleagues. Participants performed emotion work to deal with negative responses to their feminist identity, but this depleted emotional energy and created stress. Participation in movement events provided much-needed emotional support and an outlet for deviant emotions.
Keywords: 1900-1999; 1990-1999; australie; colère; discipline; militance; océanie; organisations féministes; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; étude qualitative

Chapitre XVII Sexe Et Tempérament et Conclusion dans Moeurs et sexualité en Océanie: au coeur des sociétés traditionnelles des îles Samoa et de Nouvelle-Guinée - Mead, Margaret; Chevassus, Georges (Moeurs et sexualité en Océanie: au coeur des sociétés traditionnelles des îles Samoa et de Nouvelle-Guinée, 1963)
Dans le texte Adolescence à Samoa (1928), l'auteure soutient que l'adolescence n'est pas une étape nécessaire entre l'enfance et l'âge adulte. Dans le texte Trois sociétés primitives de Nouvelle-Guinée (1935), elle analyse, à partir de ses observations de terrain, les différences de caractère entre hommes et femmes.
Section: 606 pages : illustrations ; 18 cm
Keywords: anthropologie; approches et analyses; corps; cours; discipline; océanie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; système colonial; systèmes d'oppressions; thématiques